2022
DOI: 10.1177/14680874221119131
|View full text |Cite
|
Sign up to set email alerts
|

Effect of injection timing of waste plastic oil and its blends on CRDI diesel engine

Abstract: Fossil fuels are a major global concern due to escalating demand and current geo-politics. So demand has been arising for alternative fuel for I C engines. Alternatively, the generation of waste plastic is a severe environmental problem due to global disposal issues; however, it may be converted into alternative fossil fuel with minor amendments in fueling systems. So In this study, blends of waste plastic oil (WPO) have been investigated on CRDI diesel at variable injection timings (IT) (from 26°bTDC to 14°bT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…According to the studies by Balat et al [8] and Fayad et al [9], biodiesel can be produced from more than 350 oil-bearing crops, including soybeans, castor beans, sunflowers, rapeseed, peanuts, and cottonseed, each constituting potential alternatives for fossil fuel. Kumar et al [10] investigated the effect of waste plastic oil (WPO) blends and variable injection timing on engine performance and emissions in a CRDI diesel engine. They found that the optimal BTE is 6.7% at a 17 • bTDC injection interval, and that the emissions of NO X and CO decreased by 2.15% and 16%, respectively, via the combustion of WPO compared to diesel.…”
Section: Introductionmentioning
confidence: 99%
“…According to the studies by Balat et al [8] and Fayad et al [9], biodiesel can be produced from more than 350 oil-bearing crops, including soybeans, castor beans, sunflowers, rapeseed, peanuts, and cottonseed, each constituting potential alternatives for fossil fuel. Kumar et al [10] investigated the effect of waste plastic oil (WPO) blends and variable injection timing on engine performance and emissions in a CRDI diesel engine. They found that the optimal BTE is 6.7% at a 17 • bTDC injection interval, and that the emissions of NO X and CO decreased by 2.15% and 16%, respectively, via the combustion of WPO compared to diesel.…”
Section: Introductionmentioning
confidence: 99%
“…It has been used for further research and scientific papers in the field of diesel engine processes [7]. Similar procedures of experimental determination of injection parameters, due to their crucial influence on working processes in engine cylinders, were also applied by other researchers [8][9][10][11][12][13][14][15][16]. Comparative experimental results of in-cylinder pressure flow and injection parameters in direct injection diesel engines are shown in [8], where standard diesel fuel and emulsion of water and diesel fuel are used.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of experimentally determined injection pressures on performance, power and fuel consumption in direct injection diesel engines is discussed in detail in [11], [13] and [15]. Calculated process parameters of the injection of a medium-speed diesel engine using a computer program developed for this purpose successfully corresponded to the measured [12], and in [14] it was experimentally proven that oils obtained from waste plastic may have similar injection characteristics to petroleum-based diesel fuel. By experimental determination of the pilot injection times, main injection quantities and times, combined with mathematical models of fuel dispersion, combustion and exhaust emissions, it was possible to determine the influence of the mentioned parameters on performance, noise and exhaust emissions of diesel engines [16].…”
Section: Introductionmentioning
confidence: 99%
“…Research findings suggest that incorporating plastic oil into diesel engines can enhance performance and diminish emissions. A study conducted by Kumar et al [3] illustrated that substituting 20% plastic oil for diesel resulted in a 6.7% increase in Brake Thermal Efficiency (BTE) and lowered NOx and CO emissions by 2.15% and 16%, respectively. Mustayen et al [4] observed notable improvements in torque and horsepower when utilizing plastic oil in diesel engines.…”
Section: Introductionmentioning
confidence: 99%